Beyond transactions: Understanding the determinants of e-satisfaction in online shopping - Utama, Iston Dwija; Sudirman, Ivan Diryana; Kurnianingrum, Dian (Journal of Asian Scientific Research, 2024)
This study aims to investigate the factors influencing e-commerce satisfaction, focusing on application design, merchandise attributes, transaction capabilities, and security and privacy. Internet penetration has massively changed the behavior of the customer, especially their buying behavior, from traditional to online through various channels such as e-commerce. The key finding from the quantitative approach with purposive sampling is the highly positive relationship between application design and e-satisfaction. The findings of the study demonstrate a moderate association between merchandise attributes and e-satisfaction, emphasizing the significance of product variety and presentation. Furthermore, the study has recognized other significant variables that lead to e-satisfaction, such as fast transaction capabilities and adequate security and privacy protections. The findings provide theoretical insights as well as practical guidelines, implying that e-commerce platforms may improve their customer satisfaction by prioritizing user-friendly, ease-of-use, and appealing application designs, broad product offers, streamlined transaction processes, and robust security and privacy. This study also provides future research recommendations and limitations.